Analisis Tindak Pidana Secara Bersama-Sama Tanpa Hak Menggunakan Merek Orang Lain - Ezer, Alaagapedo Eben; Hartanto; Mardani (VISA: Journal of Vision and Ideas, 2025)
With the development of trade in goods and services, trademarks play a crucial role in identifying products. Trademarks are graphical signs, including logos, names, words, letters, symbols, numbers, arrangements, and colors, used in the trade of goods or services. Given the increasing number of human needs, it is unsurprising that counterfeiting of trademarks by irresponsible individuals has become a concern, affecting both the utility and quality of the goods they sell. The purpose of this study is to analyze criminal acts related to the unauthorized use of other people's brands, focusing on case number 84/PID. B/2023.PN.Smg and case number 892/Pid. B/2020.PN. The benefit of this research is to contribute to the development of criminal law, particularly in the juridical analysis of trademark crime cases. The research method used in this study is qualitative descriptive, utilizing a theoretical approach to trademark studies, judges' considerations, and rulings in trademark abuse cases. The study revealed that in both rulings, the defendants were proven to have violated trademark rights by producing counterfeit trademarks, leading consumers to purchase these goods at the same price as genuine ones, but with inferior quality. The perpetrators gained personal benefits from the misuse of the trademarks.